Determinants of Weight Loss in an Interdisciplinary Long-Term Care Program for Childhood Obesity. (25th September 2012) - Dubuisson, A. C.; Zech, F. R.; Dassy, M. M.; Jodogne, N. B.; Beauloye, V. M.
Abstract : Background . Efforts are needed to improve the long-term efficiency of childhood obesity treatment. To adapt strategies, the identification of subgroups of patients with a greater weight loss may be useful. Objective. To analyze the results of a chronic care program for childhood obesity and to determine baseline factors (medical, dietary, and psychosocial) associated with successful weight loss. Subjects and Method. We set up a family-targeted and individually adapted interdisciplinary long-term care program. We reviewed the medical files of 144 children (59 boys and 85 girls; 10.5 ± 3.1  y; mean BMI- z -score: 2.73 ± 0.62 ) who had ≥2 interdisciplinary visits and ≥1-year treatment. Results. Mean treatment length was 2.2 y (1–6.7 y) with 3 ± 1 visits/year. The duration of treatment did not depend on the initial weight loss, but this was predictive of the weight change over time. Furthermore any additional weight loss was observed with time whatever the initial weight change. High levels of physical activity and daily water intake from baseline conditions were associated with a greater weight loss after 9 months of intervention. In contrast, a high baseline consumption of soft drinks resulted in lower weight loss. Family specific factors such as being a single child or the child's family support were identified as baseline factors which may contribute to better results. Conclusion. Our study suggests that the benefit of a chronic weight control program supports the need for its integration into the current concept of treatment. Better prevention policy and parental support may improve the success of the childhood obesity treatment.